Physical examination performed by the international military operations in mountainous terrain - Fedak, S.S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : test the author’s program of physical training in order to adapt the Armed Forces of Ukraine to the military profession in international operations in various climatic conditions. Material : the study involved 67 military first age group - employees under contract. Analyzed growth performance, body weight, lung capacity, sample Stange, carpal dynamometry, heart rate at rest, systolic and diastolic blood pressure recovery time heart rate to baseline after 20 sit-ups in 30 seconds, adaptive capacity, Quetelet index, Robinson, step test, physical condition, life and power indices. Results : the effect of physical training lessons the author’s program on the physical condition of the peacekeepers, international activities which took place in the highlands. As a result, training peacekeepers marked stable operation of the cardiovascular system and respiratory system. This increases the stability of the organism to adverse environmental factors. Conclusions : the positive influence of employment on the program developed by the military on the body.